Do Primary Care Physicians Contribute to the Immunization Status of Their Adult Patients? A Story of Patients' Overconfidence Coupled With Physicians' Passivity - Papis, Thibaut; Clavien, Christine (Frontiers in Medicine, 2021)
Context: Immunization coverage counts among the priorities of public health services. To identify factors that motivate or fail to motivate patients to update their vaccination status would help to design future strategies and awareness campaigns. Objective: Our aim was to assess the impact of primary care physicians on the immunization status of their adult patients, and to explore possible explanations. Methods: We invited students and collaborators of Geneva University to bring their paper vaccination records to receive an assessment of their immunization status and personalized vaccination recommendations. Participants completed a first questionnaire at the recruitment phase, and a second 2-3 months later. We assessed their immunization status with the viavac© algorithms based on the Swiss national immunization plan. Results: Having a primary care physician did not correlate with better immunization status: only 22.5% patients who reported having a physician and 20% who reported having no physician were up-to-date (n=432; p>0.5). A linear regression indicates that the frequency of medical consultations did not affect patients’ immunization status either. Even the participants who recently showed their vaccination record to their primary care physician did not have a better vaccination status. We explored possible explanatory factors and found evidence for the patients’ overconfidence about their own immunization status: 71.2% of the participants who predicted that they were up-to-date were wrong about their actual status, and 2-3 months after having received their immunization assessment, 52.8% of the participants who ‘remembered’ having received the assessment that they were up-to-date were wrong: they had in fact received the opposite information that they were not up-to-date. This substantial proportion of wrong beliefs suggests that adult patients are unworried and overconfident about their own immunization status, which is likely to induce a passive resistance towards vaccination updating. Conclusions: This study indicates that the vaccination coverage and beliefs of adults about their immunization status is suboptimal, and that primary care physicians need further support to improve their health-protection mandate through routine immunization check-ups. We highlight that the current covid vaccination campaigns offer a rare opportunity to update patients’ immunization status and urge physicians to do so.